Flowering and fruiting of Ananas comosusL. Merr. in two cultivation systems under subtropical conditions - Levin, Sebastian (2019)
Pineapple production in the subtropics is limited bylow temperatures.Frost affects the growth and development of the plants, being the main factor that compromises production. One way to mitigate this problem is theuseofplastic covers(greenhouses), which could, however,negatively affect the productivity. We studied theflowering and fruiting of pineapple (Ananas comosusL. Merr.) in two cropping systems (greenhouse and field) in asubtropical regionin the northeast of Argentina. Two experimental batches, with plastic covers and uncovered, divided into eight plots,were set up and phenological crop monitoring was performed. The experimental design was completely random.At the time of harvest,physical and chemical variables, suchas lengthof fruit length with crown, fruit length without crown, equatorial diameter, density, firmness, °Brix and acidityvalues,were analysedto representfruit quality. The results showed significant differences between the cultivation systems studied. Cultivation type had a marked effect on fruit quality; fruits produced in the greenhouse had a higher weight and size than thoseproduced in the field; however,the chemical variables related to flavour did not differ significantly between the two cultivation types.